2021
DOI: 10.4314/ahs.v21i1.10s
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and outcomes of early infant male circumcision services in four counties in Western Kenya

Abstract: Background: Early Infant Male Circumcision (EIMC) is part of sustainable HIV prevention strategies in Kenya. The goals of the national EIMC program are to circumcise at least 40% of all newborn male infants delivered at hospitals offering the service and keep the rate of moderate and adverse events below 2%. Objectives: To determine the proportion of early male infants (age less than 60 days) born at hospitals in four counties of western Kenya who got circumcised and document the prevalence of adverse ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…In contrast to findings from African RCTs of circumcisions carried out in adolescence and adulthood, which together suggested 58% efficacy of VMMC in providing short and intermediate term prevention of HIV [2][3][4][5], our national cohort study with up to more than three decades of follow-up found no reduction in risk of HIV or other STIs following circumcision in infancy or childhood. Consequently, our findings question the relevance and justifiability of ongoing efforts to expand VMMC programs in Africa to also cover circumcision of male infants and boys under 15 years of age [22][23][24][25]. If childhood circumcision provides no protection against the acquisition of HIV and other STIs in adulthood, as our findings and those of the Dunedin cohort study suggest [34], this knowledge should inform debates over the practice of non-therapeutic circumcision of male minors [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…In contrast to findings from African RCTs of circumcisions carried out in adolescence and adulthood, which together suggested 58% efficacy of VMMC in providing short and intermediate term prevention of HIV [2][3][4][5], our national cohort study with up to more than three decades of follow-up found no reduction in risk of HIV or other STIs following circumcision in infancy or childhood. Consequently, our findings question the relevance and justifiability of ongoing efforts to expand VMMC programs in Africa to also cover circumcision of male infants and boys under 15 years of age [22][23][24][25]. If childhood circumcision provides no protection against the acquisition of HIV and other STIs in adulthood, as our findings and those of the Dunedin cohort study suggest [34], this knowledge should inform debates over the practice of non-therapeutic circumcision of male minors [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 80%
“…Such an approach was appropriate because the average periods of follow-up were almost identical in the compared groups, being 21.8 years among intact males and 21.6 years among circumcised males. Among international organizations and stakeholders arguing in favor of circumcision in the fight against HIV in Africa, the expectation is that infant or childhood circumcision will provide the same, or an even higher, degree of HIV protection compared to what has been reported for adult male circumcision [14,[22][23][24][25]. Consequently, we tested the directional (one-sided) null hypothesis of equal or higher rates of HIV acquisition in circumcised males against the alternative hypothesis that the rate is lower among circumcised males.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations